Freeze-thaw stability of oil-in-water emulsion stabilized by nanocelluloses - Montenegro V., Josué R. (Zamorano: Escuela Agrícola Panamericana, 2019., 2019)
The freeze-thaw stability of emulsions with 40% of vegetable oil and stabilized by three types of nanocelluloses: cellulose nanofibers (CNFs), cellulose nanocrystals (CNCs) and TEMPO cellulose nanofibers (TEMPO-CNFs); were studied by visual observation, optical microscopy and rheological measurements. Cellulose nanocrystals were able to form homogeneous and low viscosity emulsions after freeze and thaw treatment at 0.3% w/v and 0.1 M NaCl. The effect of pH on oiling off was evaluated at values of 4, 5, 6 and 7. Significant differences were observed in oiling off, which represent the amount of free oil present in an emulsion. A better stability between the treatments was obtained at pH 4. Ionic strength effect was evaluated at five salt (sodium chloride) concentrations (0.0 0.01, 0.05, 0.1 and 0.2 M), finding significant differences for all the treatments excepting among 0.1 and 0.2 M, in which there was no oil separation that represent stability. Apparently, the addition of salt enhances the stability of the emulsions at values no more than 0.1 M; above this concentration, a negative effect was observed; this was due to the salting out effect. Cellulose nanocrystals had better emulsifying properties than CNFs and TEMPO-CNFs and can stabilize emulsions after freeze and thaw under specific conditions. It is recommended to study the cellulose nanocrystals behavior in the encapsulation of hydrophobic substances to be added in a hydrophilic matrix after a freeze-thaw treatment.